Report on drug demand reduction needs assessment in the Caribbean - Klein, Axel...[et al.] ([Caricom Secretariat] [Georgetown]AN, 2001)
Outlines the key challenges facing the Caribbean Community in reducing the demand for drugs. Identifies the principle areas where demand reduction activities may be further developed and enhanced.